Geometric control of quadrotor with finite-time convergence and improved transients. Issue 7 (19th May 2021) - Sharma, Manmohan; Kar, Indrani
ABSTRACT: A finite-time geometric control of quadrotor has been proposed in this paper by representing the attitude using rotation matrices to avoid the singularities and ambiguities associated with Euler angles and quaternions. One of the unique features of the controller is the use of left tracking error function to simplify controller design. A composite error function is designed and it is proved mathematically that the closed-loop attitude as well as the translational dynamics are finite-time stable. The coordinate invariant approach is another unique features of the proposed method as opposed to the literature. Numerical simulations have been provided at the end to show the effectiveness of the proposed method. Simulation results demonstrate better transient performance of the proposed control method as compared to control law presented in the literature.